Kolej Perikanan Sultan Nazrin Muizzuddin Shah (KPSN) / Nurul Ain Izzyanie Jamaluddin - Jamaluddin, Nurul Ain Izzyanie (Universiti Teknologi MARA, Perlis, 2024)
The entire 24 weeks of my industrial training at Kolej Perikanan Sultan Nazrin Muizzuddin Shah (KPSN), which started on September 1 and ended on February 9, 2023, were an eye-opening and fascinating experience for me as I worked toward finishing the Industrial Training course (HRM666). This internship's primary goal is to ensure that students may completely acquire the knowledge and skills they need to succeed in their soon-to-be fast-paced occupations. This report includes a background summary of KPSN as well as a reflection on my training in terms of the knowledge and skills I was able to acquire during my industrial training to face challenges. This comprehensive report also includes a summary of all the roles and responsibilities that KPSN assigned to me throughout my internship.